Design of Learning Media: Modeling & Simulation of Building Thermal Comfort Optimization System in Building Physics Course (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The use of instructional media is something that can support the teaching and learning process; therefore, a lecturer must have the ability to create and develop learning media. This study aims to improve student learning outcomes in building physics course by using simulation learning media and models to help students understand thermal comfort material. Making modelling and simulation media is done using MATLAB software. The subjects of this study were physics engineering students who took Building Physics course. At the beginning of the study, students are given material and then in groups discuss thermal contents and then given a pretest test with an average score of 70.27, and for an average grade of 71.3 assignments. At the meeting next week, using the Student-Centered Learning (SCL) method and using problem-based learning in groups, students take temperature measurements in several rooms in the Building at the UNAS Physical Engineering Laboratory. The measurement results show that the room does not have thermal requirements (PERGUB No. 38/2012), so students have the task of conducting experiments using models that have been created by researchers to create learning media to improve comfort in using thermal buildings. Simulation results carried out by students, that is, can produce rooms with thermal conditions at 21-25Â°C (PERGUB No. 38/2012). This simulation is also able to provide the score of building energy efficiency. After students succeed in conducting the test, the assessment test or posttest is carried out with an average score obtained 80.55, and an average score of 80 assignments. The results of the pretest, assignment 1, assignment 2, and posttest show an increase in studentsâ€™ scores of 14.6% for the Test and Task Score of 12.20%. Based on the hypothesis test, for both variables showed t-count t-table and significance 0.05. It shows there are significant differences in student learning outcomes both test scores and assignment scores before and after using a simulated media. Thus, the system and simulation model designed can be used as learning media that can improve student learning outcomes.